2016
DOI: 10.1136/ejhpharm-2016-000904
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar infliximab for the management of rheumatoid arthritis in France: what are the expected savings?

Abstract: ObjectivesBiosimilar infliximab, the first similar biological medicinal product containing monoclonal antibodies to be commercialised, is likely to contribute to a significant reduction in healthcare costs. We aimed to assess the cost savings potential over 1 year of the use of biosimilar infliximab for the treatment of rheumatoid arthritis (RA) patients in Alsace and in France, in a real-life setting.MethodsThe analysis was based on a previously conducted observational study which evaluated the annual cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Furthermore, in the study by Hemmington et al [ 21 ] 21.3% of specialised physicians indicated that they would explain to their patients that biosimilars are a cost-effective option. The usage of biosimilars may allow facilities to save costs; in some countries and under certain circumstances biosimilars can be much cheaper than reference medicines and more patients could receive this modern therapy [ 23 25 ]. Community and hospital pharmacists (92%) from France indicated “Health care costs savings” as their motivation to promote the prescribing of biosimilars [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the study by Hemmington et al [ 21 ] 21.3% of specialised physicians indicated that they would explain to their patients that biosimilars are a cost-effective option. The usage of biosimilars may allow facilities to save costs; in some countries and under certain circumstances biosimilars can be much cheaper than reference medicines and more patients could receive this modern therapy [ 23 25 ]. Community and hospital pharmacists (92%) from France indicated “Health care costs savings” as their motivation to promote the prescribing of biosimilars [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In a previous analysis, we showed that management of rheumatoid arthritis patients with biosimilar infliximab in France could result in €13.6 million annual cost savings, enabling treatment of 1,141 additional patients if fully reallocated. 8 Many pharmacists did not feel sufficiently informed about tolerance and iatrogenic effects. However, various clinical trials provided evidence-based information to confirm that there are no meaningful differences in terms of quality, safety and efficacy between a reference biological medicinal product and biosimilar drugs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Considering this environment, the availability of biosimilar alternatives, i.e., versions of reference biological medicinal products, is critical for containing the health care expenses. [2][3][4][5][6][7][8][9] A biosimilar of infliximab has been on the European market since the beginning of 2015. Subsequently, the availability of the 6 other monoclonal antibodies listed above, in addition to many other reference biological medicinal products, may encourage the production of similar biological medicinal products when patents expire.…”
Section: Introductionmentioning
confidence: 99%
“…Several BIAs assessing the impact of the introduction of infliximab and etanercept biosimilars were found in the literature [17][18][19][20][21][22][23][24][25]. As these BIAs were conducted in different countries in Europe, the total spending on bDMARDs and bDMAIDs varies between countries and the comparisons between international budgets would be inappropriate.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A survey of the literature revealed that budget impact analyses have been performed to estimate cost savings associated with the entry of infliximab and etanercept biosimilars before and after their market entry at national and international levels [16][17][18][19][20][21][22][23][24][25]. The majority of these budget impact analyses were based on third-party payer perspective (public health systems, payers, patients, and healthcare professionals).…”
Section: Introductionmentioning
confidence: 99%